Trophic Interaction of Spodoptera frugiperda and their Egg Parasitoids in Agricultural Landscape - Kalinyo, Daniel; Andrianto Kupepe; Dendi Ferdianto; Ismail Djamaludin; Hiksa Maulana Saputra; Mihwan Sataral (Faculty of Agriculture, Tompotika Luwuk University, 2024)
Trophic interactions between Spodoptera frugiperda and its parasitoids are crucial for effective biological control strategies. Understanding these interactions is essential for developing methods that mitigate pest impacts on crops while preserving agroecosystem balance. This study aims to (a) evaluate the interactions between S. frugiperda and its parasitoids, (b) explore the relationship between landscape composition and parasitism levels of S. frugiperda, and (c) analyze how landscape composition influences the food web metrics of S. frugiperda and its parasitoids. The findings identified three egg parasitoid species—Telenomus sp1, Telenomus sp2, and Trichogramma sp—parasitizing S. frugiperda, with Telenomus sp1 emerging as the dominant parasitoid and a potential biological control agent. Notably, landscape composition did not significantly affect the parasitization rate of S. frugiperda eggs. However, the age of maize plants positively influenced the parasitization rate, indicating that older plants may enhance the parasitization of S. frugiperda eggs. Landscape composition, particularly in agricultural contexts, positively influenced Shannon diversity while negatively affecting interaction evenness. In contrast, semi-natural habitats enhanced interaction evenness. These findings highlight the significance of landscape composition in understanding the complexity of the S. frugiperda-parasitoid food web, providing valuable insights for developing pest control strategies for S. frugiperda and conserving natural enemies.